2017
DOI: 10.1007/s00261-017-1088-5
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal schwannomas: review of imaging findings and pathology

Abstract: Schwannomas are typically slow growing, encapsulated benign neoplasms. Visceral schwannomas are rare, and preoperative diagnosis is challenging, as they are often confused with other neoplasms even with advanced imaging studies. Surgical excision is usually needed to establish a definitive diagnosis, as pathology is the "gold standard." We review the imaging findings of abdominal schwannomas focusing on pancreatic, gastrointestinal, and retroperitoneal/adrenal schwannomas with pathology correlation. We conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 53 publications
1
51
0
2
Order By: Relevance
“…Compared with their counterparts arising in the head and neck or extremities, retroperitoneal schwannomas have a higher tendency to undergo spontaneous cystic degeneration . Cystic change is also the major feature of primary adrenal schwannoma, which usually can be detected on CT and MRI . In the present study, two types of intralesional cystic areas were found in the 11 cases, and a multiseptated cystic appearance was the most frequent form.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…Compared with their counterparts arising in the head and neck or extremities, retroperitoneal schwannomas have a higher tendency to undergo spontaneous cystic degeneration . Cystic change is also the major feature of primary adrenal schwannoma, which usually can be detected on CT and MRI . In the present study, two types of intralesional cystic areas were found in the 11 cases, and a multiseptated cystic appearance was the most frequent form.…”
Section: Discussionmentioning
confidence: 43%
“…In the present study, two types of intralesional cystic areas were found in the 11 cases, and a multiseptated cystic appearance was the most frequent form. Although the appearance of cystic change on CT and MRI has been reported, this is the first detailed US description of the different forms of cystic change of adrenal schwannomas.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For retroperitoneal masses larger than 4 cm, especially those with clinical symptoms, surgical removal is regarded as the most rational way, with the benefit of both diagnosis and therapy. An incomplete excision may increase 5-10% of local recurrence (7). Moreover the possibility of malignancy is considerable.…”
Section: Discussionmentioning
confidence: 99%